The efficacy of the pocket-creation method for cases with severe fibrosis in colorectal endoscopic submucosal dissection - Yoshida, Naohisa (Endosc Int Open, 2018)
BACKGROUND AND STUDY AIMS:  Severe fibrosis poses a challenge in colorectal endoscopic submucosal dissection (ESD). Recently, the pocket-creation method (PCM) has been developed for overcoming various difficulties of ESD. A specific tapered hood is used for adequate traction in the PCM, and endoscopic operability becomes stable in the pocket. In this study, we investigated the efficacy of the PCM in ESD for cases with severe fibrosis. PATIENTS AND METHODS : We retrospectively reviewed 1000 consecutive colorectal ESD cases (April 2006 to January 2017). Since 2016, the PCM was performed in 58 cases. The indications for ESD included (1) tumors ≥ 20 mm in size diagnosed as intramucosal cancer or high-grade dysplasia and part of T1a cancer using magnifying endoscopic examinations and (2) tumors that appeared impossible to resect with endoscopic mucosal resection because of suspected fibrosis. We identified 120 cases with severe fibrosis and compared them to cases without severe fibrosis. Additionally, the 120 severe fibrosis cases were divided into the PCM and non-PCM groups. En bloc resection, procedure time, discontinuation, and complications were analyzed between these 2 groups. RESULTS:  Among all 1000 ESDs, severe fibrosis and discontinuation rates were 12.0 % (120 cases) and 1.8 % (18 cases), respectively. Regarding the comparison between cases with severe fibrosis and with no severe fibrosis, there were significant differences about en bloc resection rate (78.3 % vs. 95.7 %, P  < 0.001), discontinuance rate (12.5 % vs. 0.3 %, P  < 0.001), and perforation rate (8.3 % vs. 2.6 %, P  = 0.001). Among the 120 cases with severe fibrosis, 21 and 99 cases were in the PCM and non-PCM groups, respectively. The PCM group had a higher en bloc resection rate (95.2 vs. 74.7, P  =  0.03), a shorter mean procedure time (min) (79.6 ± 26.5 vs. 118.8 ± 71.0, P  = 0.001), and no cases of discontinuation. An analysis of the interobserver agreement for the diagnosis of severe fibrosis among the 3 endoscopists showed kappa values of > 0.6. CONCLUSIONS:  In cases with severe fibrosis, the PCM with ESD improved en bloc resection rates and shortened the procedure time compared to the conventional non-PCM method. Additionally, the PCM reduced the discontinuation rate.